(untitled) (Olhar de Professor, 2025)
We discuss the possibility that teachers maintain the autonomy to develop their own classes in the face of international circulation of knowledge. To this end, we propose a historical review that: a) revisits the introduction of Linguistics in Brazilian universities and its relationship with the teaching of Portuguese; b) points to a shift in the proposed relationship between linguistic research and language teaching concomitant with the adoption of teaching standardization policies from the 1990s onwards; c) describes the policies in force since then as based on an “ecumenical” principle that has been dislodging national scientific production in favor of an increased circulation of postulates originating from research carried out abroad. Towards the end, we examine two examples of classes prepared by teachers that show: a) movements of relative preservation of autonomy for decision-making; b) the reproduction of trends linked to the massification and internationalization of educational knowledge.